Yield strength increase of a CoCrNi medium entropy alloy by interstitial nitrogen doping at maintained ductility. (15th March 2020) - Moravcik, Igor; Hadraba, Hynek; Li, Linlin; Dlouhy, Ivo; Raabe, Dierk; Li, Zhiming
Abstract: We show that interstitial nitrogen doping improves the tensile properties of a CoCrNi alloy. A material with 0.5 at% interstitial nitrogen was compared to a nitrogen-free CoCrNi alloy. The nitrogen-doped variant has a stable, single-phase face-centered cubic (FCC) lattice structure without nitrides, also after different annealing treatments (800–900 °C, 10 and 30 min). The nitrogen caused an increase in yield strength by 24–33% at identical ductility compared to the nitrogen-free material with similar grain size. The strengthening effect of nitrogen was explained in terms of the simultaneous increase of the lattice friction stress and of the Hall-Petch coefficient. Graphical abstract: Image, graphical abstract